2020
DOI: 10.1021/acs.inorgchem.0c01125
|View full text |Cite
|
Sign up to set email alerts
|

B(C6F5)3-Catalyzed Dehydrocoupling of POSS Silanols with Hydrosilanes: A Metal-Free Strategy for Effecting Functionalization of Silsesquioxanes

Abstract: We report a highly effective metal-free catalytic procedure for the functionalization of silsesquioxanes via dehydrocoupling of various POSS silanols with hydrosilanes in the presence of commercially available tris­(pentafluorophenyl)­borane B­(C6F5)3. This approach enables the unprecedented one-pot synthesis of valuable silsesquioxane derivatives under mild conditions, with no corrosive byproducts formed in the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Recently, our group developed a variety of synthetic procedures utilizing mainly hydro- [61][62][63][64] and allylsilanes in the O-silylation reactions. [65][66][67][68][69][70] Given all this, we decided to investigate the possibility of obtaining the Si-OR and Si-O-Si′ moieties by using alkynylsilanes in a reaction with hydroxy-substituted com- pounds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group developed a variety of synthetic procedures utilizing mainly hydro- [61][62][63][64] and allylsilanes in the O-silylation reactions. [65][66][67][68][69][70] Given all this, we decided to investigate the possibility of obtaining the Si-OR and Si-O-Si′ moieties by using alkynylsilanes in a reaction with hydroxy-substituted com- pounds.…”
Section: Introductionmentioning
confidence: 99%
“…4 On the other hand, accurately positioning functional groups in custom-designed architectures through precise synthesis can be an overwhelming challenge. [5][6][7][8][9][10][11][12][13] So far, little reliable evidence has been presented for obtaining POSSs with several (less than 8 in the case of octasubstituted derivatives) reactive substituents. 14 There is also a lack of information on this type of organosilicon compounds' crystal structures.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Panisch et al [29] reported the functionalization of all-cis-cyclotetrasiloxanes via the Heck and Sonogashira coupling reactions. The Piers-Rubinsztajn reaction, an efficient route for constructing the C-O-Si or Si-O-Si bonds [40,45,[62][63][64][65][66][67], can also be used for the modification of hydrosilanes and hydrosilyl-functionalized linear, hyperbranched, cage T8, and double-decker silsesquioxanes [40,45,[62][63][64]66,[68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. In the case of all-ciscyclotetrasiloxanes, we recently synthesized and characterized Janus-type phenyl-substituted all-cis-cyclotetrasiloxanes, as shown in Scheme 1 [35].…”
Section: Introductionmentioning
confidence: 99%